Quality of Public Service at the Lemahabang District Office, Karawang Regency in Making Job Seeker Identity Cards (AK-1) - Andini Novitasari; Eka Yulyana; Lina Aryani (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to examine and analyze the quality of public services at the Lemahabang District Office, Karawang Regency in Making Job Seeker Identity Cards (AK-1). This study uses the concept of a descriptive qualitative approach with triangulation of data collection which includes interviews, observations and documentation to then be analyzed using the Miles and Huberman model, namely reduction, presentation and conclusion drawing. The discussion of this research is reviewed in accordance with the principle of public services based on Public Service Standards according to (Decree of the Minister of PAN and RB number 63/KEP/M.PAN/7/2003 concerning General Guidelines for the Implementation of Public Services) which include service procedures, completion time, service costs , service products, facilities and infrastructure and competence of service officers. The results of the study indicate that it is still necessary to optimize the facilities and infrastructure sector where there must be additional computers, printers and repairs to the waiting room for the community. The rest of the making of the Job Seeker Identity Card (AK-1) carried out by Lemahabang District has been running according to the procedures determined by the Karawang Regency Manpower Service.